Community-based Lifelong Learning for Promoting Health in Older Adults: A Qualitative Analysis of a Continuing Education Program for Seniors in Toronto - Miya Narushima (Adult Education Research Conference, 2007)
This case study of the Seniors Daytime Program, a continuing education program run by the Toronto District School Board, examines the roles and benefits of community-based lifelong learning for the post-work population and, in particular, seniors at risk from the perspectives of adult education and health promotion.